2017
DOI: 10.1007/s11248-017-0024-3
|View full text |Cite
|
Sign up to set email alerts
|

MsmiR156 affects global gene expression and promotes root regenerative capacity and nitrogen fixation activity in alfalfa

Abstract: MicroRNA156 (miR156) regulates a network of downstream genes to affect plant growth and development. We previously generated alfalfa (Medicago sativa) plants that overexpress homologous miR156 (MsmiR156OE), and identified three of its SPL target genes. These plants exhibited increased vegetative yield, delayed flowering and longer roots. In this study, we aimed to elucidate the effect of miR156 on the root system, including effect on nodulation and nitrogen fixation. We found that MsmiR156 overexpression incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 66 publications
1
42
0
Order By: Relevance
“…Notably, this phenomenon seems to be evolutionarily conserved. The same positive relationship between miR156 level and rooting capacity has been found in Malus xiaojinensis and Medicago sativa (Aung et al, 2017;Xu et al, 2017). However, the molecular mechanism by which miR156/SPL regulates root regenerative capacity is poorly understood.…”
Section: Introductionmentioning
confidence: 70%
“…Notably, this phenomenon seems to be evolutionarily conserved. The same positive relationship between miR156 level and rooting capacity has been found in Malus xiaojinensis and Medicago sativa (Aung et al, 2017;Xu et al, 2017). However, the molecular mechanism by which miR156/SPL regulates root regenerative capacity is poorly understood.…”
Section: Introductionmentioning
confidence: 70%
“…Another study proposed a role of miR156OE and SPL13i in heat stress tolerance since plants carrying these constructs showed increased antioxidant levels (Matthews et al, 2019). As found by NGS, plants possessing miR156OE exhibited broad changes in gene expression, including genes involved in nodulation, root development and phytohormone biosynthesis (Aung et al, 2017). Taking together, miR156 can improve drought or heat stress tolerance in alfalfa, at least partially by silencing SPL13 (Feyissa et al, 2019;Matthews et al, 2019).…”
Section: Resistance To Abiotic Stressmentioning
confidence: 86%
“…In this study, we found that the OsmiR156regulated OsSPL3 and OsSPL12 repress adventitious root development in rice ( Figures 6C and 11). miR156 was reported to affect rooting in several species (Chuck et al, 2007;Zhang et al, 2011;Feng et al, 2016;Aung et al, 2017;Massoumi et al, 2017;Xu et al, 2017). In maize (Zea mays), corngrass1 mutants have elevated miR156 levels and produce more crown roots (Chuck et al, 2007).…”
Section: The Mir156-spl Module Is Probably a Conserved Regulator Of Amentioning
confidence: 99%